High-Resolution Image Analysis Reveals a Decrease in Lens Thickness and Cone Density in a Cohort of Young Myopic Patients - Xin, Xiaoyu; Guo, Qingge; Ming, Shuai; Liu, Changgeng; Wang, Zhongfeng; Lei, Bo (Frontiers in Medicine, 2021)
Purpose: To study the association between axial length (AL) and the thickness of lens, retina, choroid and cone density with swept source optical coherence tomography (SS-OCT) and adaptive optics (AO) fundus camera. Design: A prospective cross-sectional study. Methods: This study included 136 eyes in 68 subjects. SS-OCT was used to quantify the thickness of lens, ganglion cell complex (GCC) layer, inner nuclear layer (INL), outer retinal layer (ORL) and choroid layer. AO was used to quantify spatial features of the cone photoreceptors, including density, spacing, regularity and dispersion. The associations among the AL and the thickness of lens, retina, choroid and cone features were evaluated with liner regression. Results: With the severity of myopia, the increased AL was associated with thinning of the lens (P < 0.001, 95% CI: -100.42 to -49.76). The thickness of ORL and choroid decreased significantly (all P < 0.001), whereas the thickness of the GCC and INL decreased only in the outer ring (both P < 0.01). There was significant correlation between cone density/spacing with AL (both P < 0.001). Although cone density was reduced from 25160/mm2 to 19134/mm2 in the inner region and from 17458/mm2 to 13896/mm2 in the outer region, their best corrected visual acuity was 20/20 or greater. Conclusions: We found the lens thickness (LT), ORL and cone density decreased in myopia. While decreasing of cone density and ORL thickness should be related to axial elongation, decreasing of LT might imply intrinsic physical accommodation. These results provide further morphological changes of myopia.